Post-Acute Sequelae of COVID-19 (PASC) in Pediatrics: Factors That Impact Symptom Severity and Referral to Treatment - Catherine M. Soprano; Ryan Ngo; Casey A. Konys; Ashley Bazier; Katherine S. Salamon (MDPI AG, 2023)
The post-acute sequelae of COVID-19 (PASC) is a complex condition. While there are emerging studies on its effects in adults, there is scarce research regarding the long-term effects of COVID-19 infection among youth. Several researchers have likened long-haul COVID-19 to chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) and postural orthostatic tachycardia syndrome (POTS). In adults, the prognosis for these diagnoses is less promising than that in youth; however, there is currently very little information available on the presentation of youth with PASC. A better understanding of the specific symptom presentation for youth diagnosed with PASC is necessary. Retrospective chart reviews were conducted collecting demographic data, COVID-19 symptoms and disease progression, and vaccination status. Additional data on referrals to a PASC treatment program and appointments attended were collected. Overall, data suggested that youth present with less severe PASC symptoms than adults, and the role of vaccination is unclear. These youth are often not referred to treatment programs. More exploration is necessary to continue to build an understanding of how best to aid youth diagnosed with PASC.